ANALISIS MODEL REGRESI LOGISTIK BINER DALAM MENENTUKAN FAKTOR-FAKTOR YANG MEMPENGARUHI MASA STUDI MAHASISWA - Dian Yulis Wulandari; Ismaraidha Ismaraidha; Ocdy Amelia (Universitas Islam Sumatera Utara, 2022)
Binary logistic regression is a statistical method that analyzes the relationship between response variables that have two or more categories with explanatory variables with a dichotomous scale (2 categories). The Binary logistic regression model can be used to determine the factors that most influence the length of the study period. The factors that influence the length of the study period in this study are academic ability, motivation, environment, lecturers, physical condition, mental, interest, talent, learning method, intelligence (IQ), and study time. The sample in this study used the sample clustering method with a total of 54 respondents and came from lecturers, employees, and students at the Panca Budi Development University. The method used is a survey using a questionnaire. Based on the results of the analysis in this study, the variable with the category of intelligence (IQ) has a partial influence on the dependent variable for the length of the study period. Simultaneously the independent variable affects the dependent variable by 41.5% and the rest is influenced by other factors. The accuracy of calcification in predicting the relationship between the independent variable and the dependent variable was 79.6%.